Long‐term effectiveness and complication rates of bladder augmentation in patients with neurogenic bladder dysfunction: A systematic review. Issue 7 (7th February 2017) - Hoen, Lisette 't; Ecclestone, Hazel; Blok, Bertil F. M.; Karsenty, Gilles; Phé, Véronique; Bossier, Romain; Groen, Jan; Castro‐Diaz, David; Padilla Fernández, Bárbara; Del Popolo, Giulio; Musco, Stefania; Pannek, Jürgen; et al.
Abstract : Aims: To systematically evaluate effectiveness and safety of bladder augmentation for adult neuro‐urological patients. Methods: The Preferred Reporting Items for Systematic Review and Meta‐analysis (PRISMA) statement was followed for review of publications. The Medline, Embase, and Cochrane controlled trial databases andclinicaltrial.gov were searched until January 2015. No limitations were placed on date or language. Non‐original articles, conference abstracts, and publications involving children and animals were excluded. Risk‐of‐bias and confounder assessment was performed. Results: A total of 20 studies including 511 patients were eligible for inclusion. The level of evidence for the included studies was low, most level 4 studies with only one level 3 study. The data were narratively synthesized. Across all studies high risk‐of bias and confounding was found. Primary outcomes were assessed in 16 of the 20 studies and showed improved quality of life and anatomical changes as well as stable renal function. The secondary outcomes were reported in 17 of the 20 studies and urodynamic parameters and continence all demonstrated improvement after bladder reconstruction. Long‐term complications continued up to 10 years post‐operatively, including bowel dysfunction in 15% of the patients, stone formation in 10%, five bladder perforations and one bladder cancer. Conclusions: Available studies are not plentiful and of relatively poor quality, appropriately designed prospective studies are urgently needed. Despite this, bladder augmentation appears to be a highly effective procedure at protecting the upper urinary tract and improving quality of life. However, it is associated with relatively high morbidity in both the short and long term.